Panorama of research in anatomy in a health school in southwestern Colombia 1970-2018 - Hurtado Valencia, Hugo (Rastros Rostros, 2024)
The objective of this article is to present an analysis of the research production of the anatomists from the Department of Morphology at Universidad del Valle, in Colombia, and the manner in which this production has been constructed during the period from 1970 to 2018. Theoretically and methodologically, the analysis is based on the guidelines of Latour & Woolgar (1979). Drawing from this approach in the sociology of science, interviews are conducted, guided visits to the anatomy section are carried out, and information is gathered from archives, databases, and libraries, allowing for the identification of periods, trends, and processes that underpin this written research production. The results reveal the existence of three periods of anatomical production corresponding to state orientations. The first, spanning from 1970 to 1977, was immersed in policies of knowledge appropriation and dissemination, supported by some American foundations. The second, inscribed within the state policies of icfes-gpd between 1985 and 1995, was focused on the production of new knowledge. And the third, occurring between 2009 and 2018, corresponds to the present time. It is concluded that over the last 50 years, the production of knowledge in anatomy has centered on the design of educational materials, anatomy applied to surgery, and the study of anatomical variations; all of which is framed within the guidelines of multilateral organizations, state policies, and the evolution of anatomy within the medical field.